Social Innovation in Community Energy in Europe: A Review of the Evidence - Hewitt, Richard J.; Bradley, Nicholas; Baggio Compagnucci, Andrea; Barlagne, Carla; Ceglarz, Andrzej; Cremades, Roger; McKeen, Margaret; Otto, Ilona M.; Slee, Bill (Frontiers in Energy Research, 2019)
Citizen-driven Renewable Energy (RE) projects of various kinds, known collectively as community energy (CE), have an important part to play in the worldwide transition to cleaner energy systems. On the basis of evidence from 8 European countries, we investigate CE, over approximately the last 50 years (c.1970-2018), through the lens of Social Innovation (SI). We carry out a detailed review of literature around the social dimension of renewable energy; we collect, describe and map CE initiatives from Belgium, France, Germany, Italy, Poland, Spain, Sweden and the UK; and we unpack the SI concept into 4 operational criteria which we suggest are essential to recognising SI in CE. These are: 1) Crises and opportunities; 2) the agency of civil society; 3) reconfiguration of social practices, institutions and networks; 4) new ways of working. We identify three main phases of SI in CE. The environmental movements of the 1960s and the “oil shocks” of the 1970s provided the catalyst for a series of innovative societal responses around energy and self-sufficiency. A second wave of SI relates to the mainstreaming of RE and associated government support mechanisms. In this phase, with some important exceptions, successful CE initiatives were mainly confined to those countries where they were already embedded as innovators in the previous phase. The third phase of CE innovation relates to the societal response to the Great Recession that began in 2007-8 and lasted most of the subsequent decade. CE initiatives formed around this time were also strongly focused around democratization of energy and citizen empowerment in the context of rising energy prices, a weak economy, and a production and supply system dominated by excessively powerful multinational energy firms. CE initiatives today are more diverse than at any time previously, and are likely to continue to act as incubators for pioneering initiatives addressing virtually all aspects of energy. However, large multinational energy firms remain the dominant vehicle for delivery of the energy transition, and the apparent excitement in European policy circles for “community energy” does not extend to democratization of energy or genuine empowerment of citizens.